Comparison of adjuvant nab-paclitaxel plus gemcitabine, S-1 and gemcitabine chemotherapy for resectable pancreatic cancer: a real-world study - Li, Haorui; Guo, Yu; Sun, Xugang; Lu, Yang; Chang, Shaofei; Wang, Xiuchao; Gao, Song; Gao, Chuntao; Zhao, Tiansuo (Frontiers in Oncology, 2023)
A survival benefit has been seen for both adjuvant nab-paclitaxel plus gemcitabine (AG) and S-1 chemotherapy compared to gemcitabine (GEM) for resectable pancreatic cancer in the APACT (2019) and JASPAC01 trials (2016), respectively. However, supporting evidence regarding the effectiveness of AG or S-1 compared to gemcitabine in real-world clinical practice remains lacking. Our study included all 246 pancreatic cancer patients who underwent surgical treatment and received postoperative adjuvant chemotherapy with AG, S-1, or GEM except for those meeting exclusion criteria (R2 resection, neoadjuvant therapy, or synchronous malignancy) at Tianjin Medical University Cancer Institute and Hospital from June 2015 to July 2021. The primary outcome was overall survival (OS) and recurrence-free survival (RFS).In total, 246 patients were included, of whom 54(22%) received adjuvant AG, 103(41%) received adjuvant S-1, and 89(37%) received adjuvant GEM. Adjuvant S-1 was associated with a prolonged OS compared to GEM (median OS S-1 vs GEM: 27.0 vs 20.0 months; HR: 0.65, P = .016) and a significantly prolonged RFS compared to GEM (median RFS S-1 vs GEM: 20.0 vs 8.2 months; HR: 0.58, P = .002). After adjusting for known prognostic factors in multivariate Cox regression analysis, this survival benefit persists and is consistent in most subgroups in our subgroup analysis. However, no statistically significant differences in OS or RFS were seen between patients treated with AG and patients treated with GEM. In this retrospective real-world study, adjuvant S-1 chemotherapy was associated with improved survival compared to GEM while no differences in OS or RFS were observed for AG compared to GEM.